1999
DOI: 10.1128/mcb.19.3.2189
|View full text |Cite
|
Sign up to set email alerts
|

The Caenorhabditis elegans Sex Determination Gene mog-1 Encodes a Member of the DEAH-Box Protein Family

Abstract: In the Caenorhabditis elegans hermaphrodite germ line, the sex-determining gene fem-3 is repressed posttranscriptionally to arrest spermatogenesis and permit oogenesis. This repression requires a cis-acting regulatory element in the fem-3 3 untranslated region; the FBF protein, which binds to this element; and at least six mog genes. In this paper, we report the molecular characterization of mog-1 as well as additional phenotypic characterization of this gene. The mog-1 gene encodes a member of the DEAH-box fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
81
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 74 publications
(85 citation statements)
references
References 39 publications
4
81
0
Order By: Relevance
“…We checked whether mog-6 was required for the splicing of several mRNAs but did not detect unprocessed RNAs. A similar result was obtained in mog-1 null mutants (Puoti and Kimble, 1999). If general pre-mRNA splicing was normal in mog-6 mutants, what might be the role of mog-6 in fem-3 regulation?…”
Section: Possible Molecular Roles Of Mog-6supporting
confidence: 64%
See 4 more Smart Citations
“…We checked whether mog-6 was required for the splicing of several mRNAs but did not detect unprocessed RNAs. A similar result was obtained in mog-1 null mutants (Puoti and Kimble, 1999). If general pre-mRNA splicing was normal in mog-6 mutants, what might be the role of mog-6 in fem-3 regulation?…”
Section: Possible Molecular Roles Of Mog-6supporting
confidence: 64%
“…Earlier studies have shown that mog-1(0) mutants produce fewer germ cells than normal (Puoti and Kimble, 1999). Similarly, mog-6 animals also made reduced amounts of germ cells (1511±117, n=22 worms analyzed) compared with wildtype hermaphrodites that contain 2400 germ cells (Kimble and White, 1981).…”
Section: Role Of Mog-6 In the Mitosis Versus Meiosis Decisionmentioning
confidence: 97%
See 3 more Smart Citations